Micro: Bit – a beginner-friendly tool to introduce coding to children / Wan Aryati Wan Ghani, Abdul Rahman Gobil and Haslinda Noradzan - Wan Ghani, Wan Aryati; Gobil, Abdul Rahman; Noradzan, Haslinda (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Micro: bit has been around since 2015, introduced by the BBC in the United Kingdom. It began with Make IT Digital initiative, aimed at inspiring young children to explore creativity in coding and programming, besides enhancing their digital literacy (Austin et al., 2020). One of the five major goals of micro: bit development is to use it inexpensively and suitable for the school setting (Austin et al., 2020). Using micro: bits, students can design and explore many real-world applications of STEM concepts from all levels:(i) beginner, (ii) intermediate, and (iii) advanced. These teach students about the global goals aligned with the Sustainable Development Goals (SDGs) to promote prosperity and protect the planet (Introducing the Global Goals | Micro: Bit, n.d.). Getting To Know Micro: Bit However, there is a significant gap in the way we approach school children, especially children with special needs and underprivileged children (Madzhi et al., 2024). Therefore, we developed a module targeted at the beginner level at the inception of this program, suitable for various groups of children. Micro:bit has served as a good teaching aid, especially for communities that have not been exposed to coding skills and the use of technology in their daily activities.